Minerals Identification of Bio-Solar Gemstone from Aceh - Akmal Nizar; Mursal Mursal; Ismail Ismail (Journal of Aceh Physics Society, 2016)
Salah satu batu mulia yang terkenal di Aceh disebut Bio-Solar. Batu permata ini banyak ditemukan di Aceh, namun, informasi detail tentang batu permata ini masih sangat terbatas. Dalam penelitian ini telah dilakukan karakterisasi batu permata Bio-Solar yang berasal dari Aceh dengan menggunakan X-Ray Florescent (XRF). Hasil penelitian menunjukkan bahwa batu permata Bio-Solar mengandung mineral-mineral CaO (59,8%), SiO2 (19,7%), Fe2O3 (11,1%), Al2O3 (7,5%), dan NiO (1,3%). Dengan membandingkan hasil ini dengan data-data penelitian sebelumnya, telah ditemukan bahwa batu permata Bio-Solar dapat diklasifikasikan sebagai jenis batu giok Vesuvianite. One of well-known gemstones in Aceh is called Bio-Solar. This gemstone is found a lot in Aceh. Nonetheless, the detail information of this gemstone is still limited. None knows if this gemstone can be classified as jade. This study has characterized this gemstone (Bio Solar) from Aceh using X-Ray Florescent (XRF). The results show that the Bio-Solar gemstone contains minerals of CaO (59.8%), SiO2 (19.7%), Fe2O3 (11.1%), Al2O3 (7.5%), and NiO (1.3%). By comparing this results to the available mineral data, we found that the Bio-Solar gemstone from Aceh can be classified as Vesuvianite jade. Keywords: Batu Giok, Bio Solar, Vesuvianite, XRF